Microstructural Investigation of Wire Failure in Wire Drawing Process - Hashim, Fadhil A.; Ihmood, Sadiq M.; Mohammed, Khalid A.; Mohsin, Ghaffar Alwan (University of Thi-Qar Journal, 2019)
This investigation concern to explain the failure operation that connected with wire drawing process. Microstructural examination was carried out for several samples of drawn wires. Copper and aluminum wires were pulled from 8 mm diameter to 3.5 mm for aluminum and to 1.75 mm for copper. The cross-sectional microstructure shows some porosity at the normal drawing condition, while no porosity at the drawing direction surface. The conclusion of this work represents that porosity will be created due to heat results from drawing process, which equal to recrystallization temperature or more, and accumulated porosity will be progressive to the final stage of wire failure.